Perspectives for Partnership and Security under the Vision of the Three Seas Initiative - Tudor, Andreea-Loredana (Acta Universitatis Danubius. Relationes Internationales, 2024)
Regional cooperation represents an important component of the geostrategic dimension of states in a certain region. The role of states and regional organizations in international relations covers the topic of security, in all its dimensions, and the form of regional security initiatives or formats. The current context of the invasion of the Russian Federation on the territory of Ukraine, led the states in the immediate vicinity, as well as the security organizations, to redefine their action, in a geopolitical logic, in the field of cooperation, including in the field of defense, for the management of external crises in the neighborhood. The Three Seas Initiative (3SI) represents one of these regional security formats, and Romania hosted the eighth Summit in September 2023, being the only state out of the 12-member states to host an I3M Summit for the second time. Hybrid threats and the current global security context led states to identify tools to provide and guarantee effective defense capabilities. The study aims to analyse the factors that determined the decision to host the 3SI Summit this year in Romania, considering the situation in the eastern neighborhood. At the same time, it is necessary an analysis the implications of this event, starting from the 2022 3SI Summit in Riga, after which Ukraine became a partner state participating in this initiative in the process of strengthening resilience. Can the 3SI format be considered, in this context, a launching pad for the rapid integration into the European structures of the Republic of Moldova, Ukraine, and Georgia?